Lobolide, a diterpene, blockades the NF-κB pathway and p38 and ERK MAPK activity in macrophages in vitro - Lv Xiao-fen; Chen Si-han; Li Jie; Fang Jian-ping; Guo Yue-wei; Ding Kan (Acta Pharmacologica Sinica, 2016)
Aim: Recent studies have shown that constitutive activation of the nuclear factor κB (NF-κB) plays a key role in chronic inflammation and cancers. The aim of this study was to characterize lobolide, a cembrane diterpene, as a drug candidate targeting the NF-κB signaling pathway. Methods: A HEK 293/NF-κB-Luc stable cell line was constructed to evaluate the effect of lobolide on NF-κB activation. THP-1 human monocytes and peripheral blood mononuclear cells (PBMCs) from healthy volunteers were tested. Lipopolysaccharide (LPS)-induced TNFα and IL-1β production and activation of the TAK1-IKK-NF-κB pathway were studied using ELISA and Western blot analysis. Results: In HEK 293/NF-κB-Luc stable cells, lobolide (0.19–50 μmol/L) inhibited NF-κB activation in a concentration-dependent manner with an IC50 value of 4.2±0.3 μmol/L. Treatment with lobolide (2.5–10 μmol/L) significantly suppressed LPS-induced production of TNFα and IL-1β in both THP-1 cells and PBMCs. In THP-1 cells, the suppression was partially caused by blockade of the translocation of NF-κB from the cytoplasm to the nucleus via affecting the TAK1-IKK-NF-κB pathway and p38 and ERK MAPK activity. Conclusion: Lobolide is a potential inhibitor of the NF-κB pathway, which blocks the translocation of NF-κB from the cytoplasm to the nucleus. Lobolide inhibits LPS-stimulated TNFα and IL-1β release, suggesting that the compound might be an anti-inflammatory compound.